Physicochemical Studies of Some Schiff Bases Derived From 6-Ethylbenzene 1,3-diol - Shipra Baluja (E-Journal of Chemistry)
The schiff bases were synthesized and their characterization was done by CHN analysis, IR and NMR spectra. The physicochemical properties such as density, refractive index, conductance, heat of solution etc., of these schiff bases were determined